Decision Framework For Enhancing The Adoption Of Alternative Infrastructure Funding Models In Ghana - Aidoo, Samuel Kojo; Makoni, Patricia Lindelwa (CSID Journal of Infrastructure Development, 2025)
This paper examines the socio-economic and infrastructure conditions that determine Ghana’s readiness to adopt alternative infrastructure funding models (AIFMs) for sustainable road development. The objective of the study is to identify the macroeconomic and sectoral drivers of AIFMs’ adoption and to develop policy frameworks for the sustainable financing of infrastructure within Ghana’s context. Ordinary Least Squares (OLS) regression analysis is applied to annual data from 2003 to 2023 to examine the relationship between macroeconomic and infrastructure indicators and economic growth , which is used as a proxy for the viability of AIFMs. The results show that employment growth, educational attainment, and road network expansion are positive contributors to growth. On the other hand, per capita income and governance indicators exhibit a negative relationship with economic growth, suggesting institutional inefficiencies and governance gaps. The impacts of access to healthcare and electricity are mixed and relatively modest, indicating that their role in the adoption of AIFMs depends on institutional and policy integration. The results highlight that fiscal capacity and socio-institutional quality affect AIFMs’ preparedness in Ghana. Based on these results, this study proposes a locally contextualised decision-making framework that incorporates macroeconomic indicators, infrastructure capacity, and social access considerations into infrastructure policy evaluation and funding decisions. The framework translates quantitative findings into a practical model for use in decision-making, providing policymakers with an effective tool for selecting sustainable AIFMs in Ghana.